2015
DOI: 10.1007/s00253-015-7157-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of secondary metabolism of Aspergillus terreus ATCC 20542 in the batch bioreactor cultures

Abstract: Cultivation of Aspergillus terreus ATCC 20542 in a stirred tank bioreactor was performed to induce the biosynthesis of secondary metabolites and provide the bioprocess-related insights into the metabolic capabilities of the investigated strain. The activation of biosynthetic routes was attempted by the diversification of process conditions and growth media. Several strategies were tested, including the addition of rapeseed oil or inulin, changing the concentration of nitrogen source, reduction of chlorine supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 65 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…The sporulation medium was as follows: agar, 30 g l −1 ; casein peptone, 5 g l −1 ; malt extract, 20 g l −1 [27].…”
Section: Methodsmentioning
confidence: 99%
“…The sporulation medium was as follows: agar, 30 g l −1 ; casein peptone, 5 g l −1 ; malt extract, 20 g l −1 [27].…”
Section: Methodsmentioning
confidence: 99%
“…This behavior was later confirmed by Boruta and Bizukojc (2016), whose results indicated that the intensive aeration scheme induced the production of (+)-geodin and terrein at the cost of lovastatin, which was found to be present at the noticeably lower concentration compared with the less aerated cultures.…”
Section: Agitation and Aerationmentioning
confidence: 54%
“…The fast tentative identification of natural products using the dereplication process can be very efficient to detect promising source of new bioactive compounds ( Kildgaard et al 2014 , Petersen et al 2014 , Boruta & Bizukojc 2015 ). In one of the fractions displaying antifungal activity, cytochalasins were identified as the active metabolites.…”
Section: Discussionmentioning
confidence: 99%